Spirituality, Organizational Commitment, and Resource Management for SDGs: Evidence from Smart Village Islamic Enterprises - Agus Supriyanto; Iwan Fahri Cahyadi; Widi Savitri Andriasari; Rina Arsiyanti (Shirkah: Journal of Economics and Business, 2026)
Despite the growing interest in Smart Villages, previous studies have paid limited attention to the role of spirituality in shaping business performance within Islamic organizations. This study aims to examine the influence of individual spirituality on organizational commitment, resource management, and business performance in Smart Village contexts. A quantitative design using Partial Least Squares Structural Equation Modelling (PLS-SEM) was employed, involving 135 respondents from Islamic organization-based enterprises in Kudus Regency, Indonesia. Data were collected through structured questionnaires using a five-point Likert scale and analyzed using SmartPLS 4 to assess measurement and structural models. The findings reveal that individual spirituality significantly enhances commitment to Islamic organizational networks, which in turn strengthens both tangible and intangible resource management. These resources partially mediate the relationship between organizational commitment and business performance. Tangible resources exhibit a stronger direct effect, while intangible resources contribute through trust, knowledge sharing, and social capital. The findings imply that integrating spirituality into organizational and resource management strategies can strengthen sustainable rural economic development within Smart Village ecosystems.